(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Reproductive healthcare (RH) services approach to men and women at their reproductive ages and ensure healthy reproduction, regulation of fertility, safe sexual practice among couples, safe pregnancy and childbirth. Various social factors are responsible for inequity in accessing the reproductive healthcare services. Objective: To find out the social pathology in accessing reproductive healthcare services of women in a selected urban area of Bangladesh. Materials and Methods: The descriptive cross-sectional study was conducted among 57 respondents to investigate the social pathologies in accessing reproductive healthcare services in Mirpur Bihari Colony of Dhaka during the period of April 2019 to May 2019. Women residing in the study area for at least 6 months and having at least one child below 10 years were included in the study. Data were collected by face-to-face interview using a semi-structured questionnaire. Result: All of the respondents were Muslim, majority (66.7%) were between age group 21-30 years and the mean±SDage was 26.67±6.48 years. Majority (64.9%) were housewives and 28.1% respondent’s husbands owned small business. The mean±SD duration of married life was 9.74±6.04 years and combined monthly income (35.1%) between 5001-10000 BDT with mean±SD income of 9,671.93±6440.41 BDT. Majority (35.1%) had 2 children at 2nd pregnancy (29.8%), without history of foetal death (78.9%). Nearly everyone (96.5%) had ANC and about half of them (49.1%) had 9 antenatal visits, 84.2% had hospital birth, 47.4% had PNC and 70.2% practiced contraception with pill (40.4%). The barriers for ANC, hospital birth, PNC, family size and contraception were expressed by 75.4%, 73.7%, 89.5%, 96.5% and 56.1% respondents respectively. ‘Poverty’ was denoted as main social pathology for ANC, hospital delivery and PNC by 72.1%, 78.6%, and 51.0% respondents respectively while ‘Husband’s wish’ or ‘Husband’s non-cooperation’ was factor for family size determination (54.5%) and contraceptive practice (43.8%). Significant association has been found between the combined monthly income and barrier to ANC (p-value <0.01), age of respondent and no of child and duration of married life (p-value <0.01). Conclusion: The women of low-income families in urban community face difficulties in accessing these services mainly due to poverty, husband’s noncooperation and unawareness. Appropriate measures should be taken to make RH services more affordable and aware couples through education and counseling for accessing these RH services. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 127-132